2021
DOI: 10.3390/s21165338
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Tool Wear and Surface Roughness Development Using Deep Learning and Sensors Fusion

Abstract: This paper proposes an estimation approach for tool wear and surface roughness using deep learning and sensor fusion. The one-dimensional convolutional neural network (1D-CNN) is utilized as the estimation model with X- and Y-coordinate vibration signals and sound signal fusion using sensor influence analysis. First, machining experiments with computer numerical control (CNC) parameters are designed using a uniform experimental design (UED) method to guarantee the variety of collected data. The vibration, soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…DL, widely regarded as the future of modern-day manufacturing, addresses bottlenecks in areas such as intelligent fault diagnosis, tool condition monitoring, and bearing fault diagnosis. There are several types of DL architectures discussed by various researchers in the area of manufacturing [109]. The most widely used architectures in DL includes convolutional neural networks [110], auto encoder [111], and recurrent neural network [112]; all these DL techniques have the advantage of automatic feature learning.…”
Section: Future Implementation and Application Perspectivesmentioning
confidence: 99%
“…DL, widely regarded as the future of modern-day manufacturing, addresses bottlenecks in areas such as intelligent fault diagnosis, tool condition monitoring, and bearing fault diagnosis. There are several types of DL architectures discussed by various researchers in the area of manufacturing [109]. The most widely used architectures in DL includes convolutional neural networks [110], auto encoder [111], and recurrent neural network [112]; all these DL techniques have the advantage of automatic feature learning.…”
Section: Future Implementation and Application Perspectivesmentioning
confidence: 99%
“…Rao et al established an optimized gray model (OGM) (1,N) to predict surface roughness and tool wear simultaneously using vibration signals [20]. Huang et al estimated tool wear and surface roughness simultaneously with one-dimensional convolutional neural network (1D CNN) and multiple sensors fusion method [21]. Similarly, Chen et al studied the applications of 1D CNN and vibration signals in tool wear detection and surface roughness estimation [22].…”
Section: Introductionmentioning
confidence: 99%
“…These layers make use of several components/techniques, such as convolutions, activation functions, pooling, dropout, batch normalisation, fully connected blocks, among others, that can be combined in multiple ways. A CNN structure can be built according to the following aspects [ 11 , 13 , 14 ]: The input data can have a 1D, 2D, or 3D format. The source of this data can be, for instance, from sensors, audio, video, and 3D images.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the scarcity of 1D CNN research, some very recent research works published on MDPI Sensors Journal can be found, e.g., the work developed by R. A. Osman et al, on interference avoidance on device communications using 5G communication; the advanced diagnosis of soft faults on motor power cables by H. Kim et al; the research “Estimation of Tool Wear and Surface Roughness Development Using Deep Learning and Sensors Fusion” presented by P.M. Huang and C.H. Lee; the monitoring of the spatter behaviours on acoustic signals developed by S. Luo et al Although all the papers cited before applied 1D CNNs on their research, neither of these very recent works used Neural Architecture Search (NAS) techniques (some do not even discuss the optimisation), resorting instead to the “traditional” grid search or trial-and-error approaches, which is the research gap that led to the need for this research [ 14 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%